Loss of mtDNA activates astrocytes and leads to spongiotic encephalopathy - Ignatenko, Olesia (Nat Commun, 2018)
Mitochondrial dysfunction manifests as different neurological diseases, but the mechanisms underlying the clinical variability remain poorly understood. To clarify whether different brain cells have differential sensitivity to mitochondrial dysfunction, we induced mitochondrial DNA (mtDNA) depletion in either neurons or astrocytes of mice, by inactivating Twinkle (TwKO), the replicative mtDNA helicase. Here we show that astrocytes, the most abundant cerebral cell type, are chronically activated upon mtDNA loss, leading to early-onset spongiotic degeneration of brain parenchyma, microgliosis and secondary neurodegeneration. Neuronal mtDNA loss does not, however, cause symptoms until 8 months of age. Findings in astrocyte-TwKO mimic neuropathology of Alpers syndrome, infantile-onset mitochondrial spongiotic encephalopathy caused by mtDNA maintenance defects. Our evidence indicates that (1) astrocytes are dependent on mtDNA integrity; (2) mitochondrial metabolism contributes to their activation; (3) chronic astrocyte activation has devastating consequences, underlying spongiotic encephalopathy; and that (4) astrocytes are a potential target for interventions.